Typhoid Fever in Children - An Update (Journal of Dhaka Medical College, 2011)
Typhoid fever is a commonly encountered systemic disease caused by the gram negative bacteria Salmonella enterica serover typhi. For the developing countries of the tropics and subtropics, it continues to be a big public health problem as the sanitation and public health standards are poor. Multidrug resistant (MDR) typhoid fever shows up a changed clinical pattern and a higher rate of complications (20%). This review article is a discussion on epidemiology, pathogenesis, clinical features, diagnosis and modern trend of treatment of typhoid fever in children. Moreover, its complication, relapse and multidrug resistant (MDR) typhoid fever are also highlited. Key words: Typhoid fever; multidrug resistant (MDR) typhoid fever; children; diagnosis; treatment. DOI: 10.3329/jdmc.v19i2.7086J Dhaka Med Coll. 2010; 19(2) : 135-143